2018
DOI: 10.1038/s41467-018-07613-z
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal control of gene expression by the pioneer factor Zelda through transient interactions in hubs

Abstract: Pioneer transcription factors can engage nucleosomal DNA, which leads to local chromatin remodeling and to the establishment of transcriptional competence. However, the impact of enhancer priming by pioneer factors on the temporal control of gene expression and on mitotic memory remains unclear. Here we employ quantitative live imaging methods and mathematical modeling to test the effect of the pioneer factor Zelda on transcriptional dynamics and memory in Drosophila embryos. We demonstrate that increasing the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
191
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(214 citation statements)
references
References 52 publications
22
191
1
Order By: Relevance
“…This "bursty" transcription has been formalized as a two state model of a promoter's activity, which cycles between ON and OFF states with stochastic rate constants (Larson, Singer, & Zenklusen, 2009;Peccoud & Ycart, 1995 The formation of PolII clusters or aggregates is thought to be driven by weak interactions between intrinsically disordered regions/low complexity domains (LCD) in PolII and other proteins (Boehning et al, 2018;Cho et al, 2018;Lu et al, 2018). Similarly, many TFs In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus. Similarly, many TFs In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus.…”
Section: Dynamics Of Dna Binding and Transcriptionmentioning
confidence: 97%
“…This "bursty" transcription has been formalized as a two state model of a promoter's activity, which cycles between ON and OFF states with stochastic rate constants (Larson, Singer, & Zenklusen, 2009;Peccoud & Ycart, 1995 The formation of PolII clusters or aggregates is thought to be driven by weak interactions between intrinsically disordered regions/low complexity domains (LCD) in PolII and other proteins (Boehning et al, 2018;Cho et al, 2018;Lu et al, 2018). Similarly, many TFs In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus. Similarly, many TFs In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus.…”
Section: Dynamics Of Dna Binding and Transcriptionmentioning
confidence: 97%
“…[ 14,18,64–68 ] Recent studies from D. melanogaster show that the establishment of accessibility is directly mediated through PTF binding sites within the enhancer, [ 14 ] and that the degree of openness positively correlates with their number. [ 65,69 ] In a classical view, while PTFs prime enhancers, they are insufficient to activate transcription of the target gene, a job left to activator TFs. [ 14,70,71 ] However, recent studies indicate that the distinction between PTFs as permissive factors and patterning TFs as instructive factors is somewhat blurred.…”
Section: Enhancer Accessibility Is Controlled At Different Scales Frmentioning
confidence: 99%
“…[ 75 ] How is this reflected at the level of their accessibility? We have seen above that accessibility of enhancers is determined by intrinsic information and quantitatively linked to the number of PTF binding sites, [ 65,69,70 ] suggesting a certain degree of autonomy. How then does the broader genomic context (e.g., nearby PREs and TREs) influence the local accessibility of an enhancer?…”
Section: Enhancer Accessibility Is Controlled At Different Scales Frmentioning
confidence: 99%
“…25,27,31 Zld cooperatively interacts with Dl by enhancing its activity near the cis-regulatory modules (CRMs) of DV genes, including that of twi. 24,[26][27][28] The cooperative effect of Zld on Dl has been previously modeled as an effective increase in the affinity of Dl for its DNA-binding site. 29 The increase in affinity could equivalently be seen as an increase in the effective Dl concentration by a factor v:…”
Section: The Effect Of Zelda On the Dorsal Gradient And Twist Exprementioning
confidence: 99%
“…[20][21][22][23] Therefore, we included in our model the activity of pioneer factor Zelda (Zld), which has been shown to make enhancer regions accessible for transcription factors and to locally increase transcription factor concentration at enhancer sites. [24][25][26][27][28] A previous model of Zld activity showed that cooperativity between Zld and Dl may help explain Dl-dependent gene expression patterns. 29 We observed that a temporal gradient of Zld stabilizes the gradient of Dl to ensure proper timing of gene expression of its targets.…”
Section: Introductionmentioning
confidence: 99%